2018
DOI: 10.1002/14651858.cd011893.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers for prevention and treatment of retinopathy of prematurity in preterm infants

Abstract: Limited evidence of low-to-moderate quality suggests that prophylactic administration of oral beta-blockers might reduce progression towards stage 3 ROP and decrease the need for anti-VEGF agents or laser therapy. The clinical relevance of those findings is unclear as no data on long-term visual impairment were reported. Adverse events attributed to oral propranolol at a dose of 2 mg/kg/d raise concerns regarding systemic administration of this drug for prevention of ROP at the given dose. There is insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Compared with previous systematic reviews ( 31 , 32 ), our study has some advantages. First, this study conducted a comprehensive search, including English databases, such as PubMed, Cochrane Library, EMBASE, and Web of Science, and Chinese databases, such as CNKI, CBM, VIP, and WanFang.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with previous systematic reviews ( 31 , 32 ), our study has some advantages. First, this study conducted a comprehensive search, including English databases, such as PubMed, Cochrane Library, EMBASE, and Web of Science, and Chinese databases, such as CNKI, CBM, VIP, and WanFang.…”
Section: Discussionmentioning
confidence: 94%
“…9,62 Activation of b-ARs in human choroidal endothelial cells using the agonist isoproterenol, increases the expression of growth factors and promotes vascular proliferation. 63 Conversely, propranolol effectively improves outcome in a model of oxygen-induced retinopathy, 64 and selective b2-AR inhibition blocks retinal 65,66 and choroidal vasoproliferation. 9 However, in the choroid the effects of propranolol have only been demonstrated in vitro in noninflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these preclinical studies, the efficacy and the safety of a treatment with propranolol, administered during the proliferative phase, was tested in human preterm newborns with ROP in a series of pilot clinical trials (Filippi et al, 2013;Makhoul et al, 2013;Bancalari et al, 2016;Korkmaz et al, 2017;Sanghvi et al, 2017;Sun et al, 2018;Ozturk and Korkmaz, 2019). Three recent meta-analyses demonstrated that oral administration of propranolol to newborns with ROP slows down the progression of retinal neovascularization and reduces the indication for laser photocoagulation or anti-VEGF drugs (Kaempfen et al, 2018;Stritzke al., 2019;Kong et al, 2021). However, treatment with propranolol aroused safety concerns because its systemic administration was responsible of life-threatening events in instable preterm infants (Filippi et al, 2013).…”
Section: Treatment With Propranololmentioning
confidence: 99%
“…This is the reason why a new trial with propranolol 0.4% eye micro-drops is planned (EudraCT number 2021-000131-31). The realistic objective of the treatment with propranolol is to obtain a reduction of ROP progression of about 60%, as is at the moment described by recent metaanalyses that have evaluated the few and small trials until now concluded (Kaempfen et al, 2018;Strizke al., 2019;Kong et al, 2021) and in line with the efficacy observed in the treatment of IHs (Léauté-Labrèze et al, 2015).…”
Section: Treatment With Propranololmentioning
confidence: 99%